An analysis of grammatical errors in Sri Mulyani's Speech at the Singapore Summit Interview - Rohit La Ami; Dinar Rosiana Mareta; Nurma Dhona Handayani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The purpose of this research is to analyze the grammatical errors found in Sri Mulyani's speech as Indonesia's Minister at the Singapore Summit (2018). The data was taken from the interview on the YouTube channel Singapore Summit, a video that was 37 minutes long. The limitations of this problem were the grammar errors and types of tenses. This study used a descriptive qualitative method. The data collection method used was observation. Data was collected by watching and hearing, and then the transcript was written. Data analyzed with grammatically incorrect words or sentences is then collected and classified based on the type of error. After all the data has been classified, the results of the study were displayed descriptively. The result found 35 data related to grammatical errors. There were three types of errors found in the use of the verb be; adding a suffix of s/es; and the past form of the verb. In the whole data source, in the use of the verb be, it was found to have 10 data. Then, it was found 20 data of adding a suffix of s/es, and an error in using tense consisted of 5 data.